Control interno del inventario del Comercial Gran Hogar del cantón Babahoyo, periodo 2021. - Villacis Nieto, Ariel Aurelio (2022)
The development of this study is directed at the internal control of the inventory of Comercial Gran Hogar, this being a fundamental part for the development of its economic activity, therefore, the need to define the knowledge regarding inventory control is important for compliance. of the objectives set, as inventory represents the asset that allows the company to generate profitability, safeguarding it is a priority, in order to examine inventory control, the contribution of other authors is necessary through the bibliographical citations that contribute to base the processes and components necessary to safeguard the inventory and in turn this contributes to the achievement of the company's objectives. For the correct evaluation of the inventory it is necessary to determine the control processes and their components, detailing each one with the purpose of establishing adequate control processes for inventory management, in that sense the generation of an inventory control environment contributes to a correct direction of the same, having as a priority the fulfillment of the outlined objectives and the protection of the inventory, carrying out risk assessments that conceive effective and efficient control activities for the success of the inventory control model.